(untitled) (Contemporary Journal of Social Science Review, 2025)
This study looks at how language education increasingly uses data from school software and adaptive learning platforms. This creates a big teaching contradiction. While these systems claim to give personalized feedback on student performance, they often turn the complex, cultural process of learning a language into simple numbers that lack context. This can accidentally favor students who speak only one language and frame others as lacking skills. This article contends that technical data skills alone aren’t enough for teachers; instead, argue that teachers need more than just technical skills to read this data. They need a "Critical Data Literacy" (CDL), built on the habit of carefully reflecting on their practice. The researcher has made a three pillar framework: Interrogate, Contextualize and Humanize, as reflective fix. This framework will turn the instructors from passive information consumers to active proponents. The proposed method helps them read dashboard analytic through an equity lens, recover their professional judgment, and map assessment to the rich realities of multilingual learners. This ideology is about denial of the data but an appeal for a considerate, thoughtful and ethical incorporation of the data into humanistic work in language teaching, proposing a pragmatic anchor between critical theory and classroom practice.